Edukasi Cerdas Memilih Makanan Sehat Gula Terbatas pada Siswa Sekolah Dasar - Hasliana Haslan; Rahmawati Rahmawati; Hasriana Hasriana (Yayasan Literasi Sains Indonesia, 2026)
People of all ages, from children to adults, enjoy sweet foods. However, Indonesia is witnessing a concerning trend regarding the consumption of added sugars. Excessive sugar intake at an early age can have long-term health consequences, including risks of obesity, diabetes, and tooth decay. Elementary school-aged children are particularly vulnerable to exposure to high-sugar foods and beverages, especially through school snacks. This community service initiative aimed to educate students on the importance of limiting sugar intake and to guide them in making healthy daily food choices. The activity took place on December 19, 2025, at SDN Inpres 5/81 Passippo in Passippo Village, Palakka District, Bone Regency, with 38 students participating. The program utilized interactive education, a simulation on selecting healthy snacks, and an evaluation component. The results indicated that most students gained a better understanding of low-sugar, healthy foods and began limiting their sugar intake by avoiding products with excessive sugar. Nevertheless, some students continued to consume high-sugar foods and beverages, highlighting the need for a sustained approach that involves both teachers and parents.